Mesenchymal stem cells expressing GD2 and CD271 correlate with breast cancer-initiating cells in bone marrow - De Giorgi, Ugo (Landes Bioscience, 2011)
PURPOSE: The bone marrow microenvironment is considered a critical component in the dissemination and fate of cancer cells in the metastatic process. We explored the possible correlation between bone marrow mesenchymal stem cells (BM-MSC) and disseminated breast cancer-initiating cells (BCIC) in primary breast cancer patients. RESULTS: The percentages of BCIC (Aldefluor(+)CD326(+)CD44(+)CD24(−)) correlated with the percentages of BM-MSC, either CD45(−)GD2(+)CD200(+)CD271(+) (Kedall's τ = 0.684, p = 0.004) or CD45(−)GD2(+)CD271(+) in the bone marrow (Kedall's τ = 0.464, p = 0.042). EXPERIMENTAL DESIGN: Bone marrow mononuclear cells (BM-MNC) were collected at the time of primary surgery in 12 breast cancer patients. BM-MNC was immunophenotyped and BCIC was defined as epithelial cells (CD326(+)CD45(−)) with a “stem-like” phenotype (CD44(+)CD24(low/−), ALDH activity). BM-MSC was defined as CD34(−)CD45(−) cells that co-expressed GD2, CD271 and/or CD200 within CD326-depleted BM-MNC. CONCLUSIONS: There was a positive correlation between mesenchymal stem cells expressing GD2 and CD271 and breast cancer-initiating cells in BM of patients with primary breast cancer.